Role of anti-DNA auto-antibodies as biomarkers of response to treatment in systemic lupus erythematosus patients: hypes and hopes. Insights and implications from a comprehensive review of the literature. (2nd November 2019) - Bragazzi, Nicola Luigi; Watad, Abdulla; Damiani, Giovanni; Adawi, Mohammad; Amital, Howard; Shoenfeld, Yehuda
ABSTRACT: Introduction : Due to the polymorphic clinical presentations and manifestations of systemic lupus erythematosus (SLE), biomarkers with enough diagnostic and prognostic value are of paramount importance. Recently, anti-double stranded DNA (anti-dsDNA) auto-antibodies have been proposed to monitor the response to different therapies. It has also been suggested that they should be employed as entry markers in trial studies. However, their clinical use remains still debated and, sometimes, controversial, due to conflicting findings reported. Areas covered : Through an extensive literature review, we evaluated changes in anti-dsDNA auto-antibodies levels before and after the administration of the treatment (either biological or non-biological). Expert opinion : Anti-dsDNA auto-antibodies related findings are still difficult to compare mainly because of the different detecting methods employed, even though in most studies included in this review a consistent decreasing pattern after the treatment seems to emerge. Hence, if properly standardized, anti-dsDNA auto-antibody profile may be a reliable biomarker to monitor the effectiveness of biologics as well as of non-biological drugs, especially if grouped in composite outcomes scores, such as the 'Lupus Multivariable Outcome Score' (LUMOS) or measured with other biomarkers, such as anti-nucleosome auto-antibodies. We recommend the assessment of anti-dsDNA auto-antibodies levels in both daily practice and research settings.